Updated results from the international phase III ALTTO trial (BIG 2–06/Alliance N063D) - Moreno-Aspitia, Alvaro (Eur J Cancer, 2021)
AIM: To present the pre-specified analyses of >5-years follow-up of the Phase III ALTTO trial. PATIENTS AND METHODS: 8381 patients with stage I-III HER2 positive breast cancer randomized to chemotherapy plus 1-year of: trastuzumab (T), oral lapatinib (L; no longer evaluated), trastuzumab followed by lapatinib (T→L), and lapatinib + trastuzumab (L+T). Primary endpoint was disease-free survival (DFS). Secondary analysis examined DFS treatment effects by hormone receptor status, nodal status and chemotherapy timing; time to recurrence; overall survival (OS) and safety (overall and cardiac). RESULTS: At a median follow-up of 6.9 years, 705 DFS events for L+T vs. T were observed. Hazard Ratio (HR) for DFS was 0.86 (95% CI, 0.74–1.00) for L+T vs. T and 0.93 (95% CI, 0.81–1.08) for T→L vs. T. The 6-year DFS were 85%, 84%, and 82% for L+T, T→L, and T, respectively. HR for OS was 0.86 (95% CI, 0.70–1.06) for L+T vs. T and 0.88 (95% CI, 0.71–1.08) for T→L vs. T. The 6-year OS were 93%, 92%, and 91% for L+T, T→L, and T, respectively. Subset analyses showed a numerically better HR for DFS in favour of L+T vs. T for the hormone-receptor-negative [HR 0.80 (95% CI, 0.64–1.00; 6-yr DFS%=84% vs. 80%)] and the sequential chemotherapy [HR 0.83 (95% CI, 0.69–1.00; 6-yr DFS%=83% vs.79%)] subgroups. CONCLUSION: T+L did not significantly improve DFS and OS over T alone, both with chemotherapy, and, therefore, cannot be recommended for adjuvant treatment of early stage HER2-positive breast cancer. TRIAL REGISTRATION: clinicaltrials.gov Identifier NCT00490139